2018
DOI: 10.1007/s00240-018-1075-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mirabegron in medical expulsive therapy

Abstract: To show the efficacy of mirabegron for medical expulsive treatment, in patients had intramural located distal ureteral stone. A 80 patients had intramural ureteral stone were assessed retrospectively between April 2017 and January 2018. Mirabegron 50 mg/day + diclofenac 100 mg/day (group 1, n = 40), and only diclofenac 100 mg/day (group 2, n = 40) were administered to patients, consecutively. Age, gender, stone size, laterality, and severity of hydronephrosis were recorded. Spontaneous stone expulsion rates (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 21 publications
5
25
1
Order By: Relevance
“…Animal experiments have also demonstrated dilatation of the ureter and a decrease in ureteral intraluminal pressure with the use of mirabegron [12]. In addition, it has been reported to be an effective and safe medical expulsive treatment agent for the reduction of distal ureteral stones with a low rate of side effects [4,14]. Mirabegron reduces the disturbing symptoms related to stents by dilatation of the ureter and decreasing intraluminal pressure [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal experiments have also demonstrated dilatation of the ureter and a decrease in ureteral intraluminal pressure with the use of mirabegron [12]. In addition, it has been reported to be an effective and safe medical expulsive treatment agent for the reduction of distal ureteral stones with a low rate of side effects [4,14]. Mirabegron reduces the disturbing symptoms related to stents by dilatation of the ureter and decreasing intraluminal pressure [15].…”
Section: Discussionmentioning
confidence: 99%
“…[3] It relaxes the bladder's smooth muscle through beta-3 agonistic effects and thus has a wide range of uses in other diseases, such as distal ureteral stones. Mirabegron has been shown to facilitate stone expulsion, especially in cases of distal ureteral stones less than 0.5 cm [4]. In this study, we aimed to investigate whether mirabegron can facilitate the passage of UAS in f-URS procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Solakhan and colleagues studied the effect of mirabegron, a beta 3 agonist, and concluded that mirabegron is efficient, safe, and a new treatment modality with a lower side-effect profile for distal ureteral stones. 16…”
Section: Discussionmentioning
confidence: 99%
“…Solakhan and colleagues studied the effect of mirabegron, a beta 3 agonist, and concluded that mirabegron is efficient, safe, and a new treatment modality with a lower side-effect profile for distal ureteral stones. 16 Sfoungaristos and colleagues demonstrated in their study that smaller size, higher serum white blood cell (WBC) count, and the presence of ureteral jet were statistically significant predictors for spontaneous stone passage. 12 Total WBC count was found to be the most significant predictor, followed by the size of the calculus.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed less pain episodes (1.02 AE 0.52 versus 1.29 AE 0.57, p ¼ 0.049). 10 In contrast, Bayar et al recently published a prospective multicentric study with 169 patients included, all with ureter stones sized between 4 and 10 mm located proximally, medially or distally. They were divided into 3 groups by randomization: group 1 was the control group; group 2 took silodosin 8 mg/day, and group 3 took mirabegron 50 mg once daily.…”
Section: Efficacy Of Mirabegron In Medical Expulsive Therapymentioning
confidence: 99%